2018
DOI: 10.3390/su10113918
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Sleep Quality as Predictors of Health in Elderly Individuals

Abstract: The main purpose of the present study was to explore the associations of sleep duration and sleep quality with self-rated health. In this cross-sectional study, participants were 894 elderly individuals. Self-rated health, sleep duration, and sleep quality were self-reported. The associations were examined using multiple logistic regression analyses.After adjusting for sex, physical activity, smoking consumption, alcohol consumption, psychological distress, socioeconomic status, and chronic disease/s, sleeping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
5
13
0
Order By: Relevance
“…This study also reported that sleep disturbance had a significant association with the health status of the patients. A similar result was found in prior studies [8][9][10][11]. The odds of poorer self-rated health was twice higher among them that were classified as having sleep disturbance [8][9][10].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study also reported that sleep disturbance had a significant association with the health status of the patients. A similar result was found in prior studies [8][9][10][11]. The odds of poorer self-rated health was twice higher among them that were classified as having sleep disturbance [8][9][10].…”
Section: Discussionsupporting
confidence: 88%
“…A similar result was found in prior studies [8][9][10][11]. The odds of poorer self-rated health was twice higher among them that were classified as having sleep disturbance [8][9][10]. Studies that were conducted in India and China also reported that sleep disturbance was a strong predictor of poor health status [12].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Men with sleep disorders are also at higher risk for suicide. Sleep disorders increase with age so that the prevalence of these disorders in the elderly in the community is more than 50% 9 …”
Section: Introductionmentioning
confidence: 99%